Implementasi Prinsip Partisipasi dan Transparansi dalam Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Cinta di Madrasah Tsanawiyah Kabupaten Kapuas - Arbainsyah Arbainsyah; ibnu elmi AS pelu (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of the Islamic Religious Education (PAI) curriculum in today's educational context no longer focuses solely on achieving students' cognitive aspects, but also emphasizes strengthening the values ​​of compassion, tolerance, and character building, supported by good educational governance. Most previous research still focused in the learning dimension in implementing the PAI curriculum. Studies that specifically integrated a love-based PAI curriculum with the principles of good governance, especially regarding stakeholder participation and transparency in the educational decision-making process, is still relatively limited. This study aimed to analyze the implementation of the principles of participation and transparency in the development of the Love-Based Islamic Religious Education Curriculum at Islamic Madrasah Tsanawiyah in Kapuas Regency. The study used a qualitative approach with a field research, through observation, interviews, and documentation techniques with madrasah principals and stakeholders at two madrasahs. Data were analyzed through stages of reduction, presentation, and drawing conclusions with source triangulation. The results indicates that the application of the principles of participation and transparency in curriculum development takes place through deliberation mechanisms, teacher council forums, and policy socialization to parents of students, while information transparency is supported by reporting learning outcomes through a digital system. Based on the spectrum Arnstein’s Ladder of Citizen Participation, the level of stakeholder participation is at the stage consultation going to partnership, as indicated by the existence of consultation and the expression of aspirations in good governance forums, yet strategic authority still rests with madrasah leaders. This finding indicates that participatory practices have gone beyond the informative stage, but have not yet fully achieved equal power sharing. Another dimension, the effectiveness of curriculum implementation is influenced by limited human resources, the use of technology, and the more evenly distributed teacher readiness within the madrasah environment. This finding emphasizes the importance of strengthening teacher capacity, supporting technology access, and developing participation mechanisms to realize more participatory and transparent madrasah curriculum governance.